2017
DOI: 10.2320/matertrans.m2016278
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Solid-State Reactive Diffusion in the Cu/Zn System

Abstract: The kinetics of the solid-state reactive diffusion between pure Cu and Zn was experimentally examined using sandwich Zn/Cu/Zn diffusion couples prepared by a diffusion bonding technique. The diffusion couples were isothermally annealed in the temperature range of 523-623 K for various times up to 49 h. Owing to annealing, an intermetallic layer consisting of the γ and ε phases was formed at the original interface in the diffusion couple, where the thickness is much smaller for the ε phase than for the γ phase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…The absence of this phase may be due to difficulties of nucleation and/or to reactions at its boundaries canceling the total growth rate of the phase. These results are consistent with those of previous studies of solid-state reactive diffusion carried out on Cu/Zn couples isothermally annealed at temperatures in the range 250-350 • C (12)(13)(14) .…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…The absence of this phase may be due to difficulties of nucleation and/or to reactions at its boundaries canceling the total growth rate of the phase. These results are consistent with those of previous studies of solid-state reactive diffusion carried out on Cu/Zn couples isothermally annealed at temperatures in the range 250-350 • C (12)(13)(14) .…”
Section: Methodssupporting
confidence: 92%
“…Cu/Zn couples prepared by diffusion bonding technique and then annealed at 300, 300, 350 and 380 • C (12) and diffusion couples investigated at 350 • C (13) indicated the formation at the Cu/Zn interfaces of only ε and γ phases. Cu/Zn couples prepared by the bonding technique and then annealed at temperatures in the range 250-350 • C showed the formation of only the ε and γ phases and that the growth kinetics of both phase layers were not parabolic (14) . On the other hand, diffusion couples investigated at temperatures ranging from 290 • C to 380 • C showed that, at all the studied temperatures, β , γ and ε phases form at the Cu/Zn interface and grow parabolically with annealing time (15) .…”
Section: Introductionmentioning
confidence: 96%
“…If interface reaction governs the layer growth, n is equivalent to unity. [37][38][39][40][41][42][43][44][45][46][47][48][49][50] As previously mentioned, the δ-Cu 4 Sn layer grows mainly into the Cu. Thus, the migration rate is greater for the Cu/Cu 4 Sn interface than for the Cu 4 Sn/Cu 3 Sn interface.…”
Section: Rate-controlling Processmentioning
confidence: 69%